SUPERVISI AKADEMIK DALAM MENINGKATKAN KOMPETENSI GURU SEKOLAH DASAR - Yudhie Suchyadi; Mira Mirawati; Fitri Anjaswuri; Dita Destiana (JURNAL MANAJEMEN PENDIDIKAN, 2022)
SUPERVISION PROCESS TO IMPROVE THE COMPETENCE OF ELEMENTARY SCHOOL TEACHERSThis study aims to determine the implementation of academic supervision by school principals in order to improve the competence of elementary school teachers in the city of Bogor. This study uses a quantitative approach with a survey method. The population of this study was the principal of a public elementary school in the area of the Teacher Working Group Cluster 2, North Bogor City District. The result of this research is that the implementation of academic supervision by the principal to increase the competence of elementary school teachers has generally been carried out well. Although there are still some principals who are still not good at carrying out academic supervision for teachers. This can be seen from: a) Teachers' perceptions of the implementation of academic supervision carried out by school principals. b) Academic supervision program compiled and implemented by the principal c) The scope of academic supervision carried out by the principal to the teacher. d) Academic supervision techniques carried out by the principal of the teacher. e) Approach to academic supervision carried out by the principal to teachers. f) There are still many factors that hinder the implementation of academic supervision. Therefore, it is necessary to have a policy from the education office that requires elementary school principals to carry out academic supervision to improve the competence of elementary school teachers in the city of Bogor.